2014
DOI: 10.1021/sb400177x
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Synthetic Biology Platform Generates Novel Chemical Structures as Scaffolds for Drug Discovery

Abstract: Synthetic biology has been heralded as a new bioengineering platform for the production of bulk and specialty chemicals, drugs, and fuels. Here, we report for the first time a series of 74 novel compounds produced using a combinatorial genetics approach in baker’s yeast. Based on the concept of “coevolution” with target proteins in an intracellular primary survival assay, the identified, mostly scaffold-sized (200–350 MW) compounds, which displayed excellent biological activity, can be considered as prevalidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
62
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 38 publications
2
62
0
2
Order By: Relevance
“…Herein, all the 1 H and 13 C NMR data of 1 were consistent with those of phenethyl 5-hydroxy-4-oxohexanoate [10]. Therefore, the structure of compound 1 was proposed as phenethyl 5-hydroxy-4-oxohexanoate, which had been previously obtained by natural product biosynthesis [10]. This is the first report of phenethyl 5-hydroxy-4-oxohexanoate (1) as a natural product.…”
supporting
confidence: 70%
See 2 more Smart Citations
“…Herein, all the 1 H and 13 C NMR data of 1 were consistent with those of phenethyl 5-hydroxy-4-oxohexanoate [10]. Therefore, the structure of compound 1 was proposed as phenethyl 5-hydroxy-4-oxohexanoate, which had been previously obtained by natural product biosynthesis [10]. This is the first report of phenethyl 5-hydroxy-4-oxohexanoate (1) as a natural product.…”
supporting
confidence: 70%
“…The key HMBC correlations between H 2 -7 and C-1/5 (G C 129.4) and C-6 (G C 139.3), and H 2 -8 and C-6 (G C 139.3) indicated that the linear part was directly connected to C-6 of the monosubstituted benzene. Herein, all the 1 H and 13 C NMR data of 1 were consistent with those of phenethyl 5-hydroxy-4-oxohexanoate [10]. Therefore, the structure of compound 1 was proposed as phenethyl 5-hydroxy-4-oxohexanoate, which had been previously obtained by natural product biosynthesis [10].…”
supporting
confidence: 67%
See 1 more Smart Citation
“…Cells harboring genetic circuits that can perform computations and retain memory of events have been engineered [Daniel et al 2013;Friedland et al 2009;Siuti et al 2014]. These genetic circuits have proven to be a significant advance in our ability to engineer cellular metabolism for bioproduction Park and Lee 2008;Yeh et al 2007], to study many dynamic cellular behaviors [Gardner et al 2000], regulate gene expression [Deans et al 2007;Endo et al 2013;Guet et al 2002;Kaern et al 2003;Levskaya et al 2009;Szulc et al 2006], detect toxic chemicals [Antunes et al 2011], create chemicals and materials to match the complexity seen in nature [Martin et al 2003], produce pharmaceutical compounds [Klein et al 2014;Ro et al 2006;Weber et al 2008], break down pollutants [Breithaupt 2006;, and function as therapeutics in vivo [Chen et al 2010;Ruder et al 2011;Smolke 2007, 2008].…”
Section: Memory and Computationmentioning
confidence: 99%
“…The screening of these novel chemicals would also help in designing biocontrol agents, eradication of many crop and animal diseases [4][5][6]. Yeast like Saccharomyces cerevisiae in the near future could also play a pivotal role in solving the energy crisis by providing biofuel [7].…”
Section: Introductionmentioning
confidence: 99%